2010
DOI: 10.1590/s0100-40422010000700003
|View full text |Cite
|
Sign up to set email alerts
|

Foam-forming properties of Ilex paraguariensis (mate) saponin: foamability and foam lifetime analysis by Weibull equation

Abstract: Recebido em 17/7/09; aceito em 15/3/10; publicado na web em 30/7/10 Saponins are natural soaplike foam-forming compounds widely used in foods, cosmetic and pharmaceutical preparations. In this work foamability and foam lifetime of foams obtained from Ilex paraguariensis unripe fruits were analyzed. Polysorbate 80 and sodium dodecyl sulfate were used as reference surfactants. Aiming a better data understanding a linearized 4-parameters Weibull function was proposed. The mate hydroethanolic extract (ME) and a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In one of these studies, the foaming power of the Camellia oleifera crude saponins extract was found be much lower than sodium laurel sulfate and Tween 80 3 . On the other hand, the foaming power of mate saponin extract was better than polysorbate 80 and sodium dodecyl sulfate 4 . In a study on the effects of tea saponins and different synthetic surfactant mixtures on foam properties, a synergistic effect was reported between saponins and cetyltrimethylammonium bromide or sodium dodecyl sulfate 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of these studies, the foaming power of the Camellia oleifera crude saponins extract was found be much lower than sodium laurel sulfate and Tween 80 3 . On the other hand, the foaming power of mate saponin extract was better than polysorbate 80 and sodium dodecyl sulfate 4 . In a study on the effects of tea saponins and different synthetic surfactant mixtures on foam properties, a synergistic effect was reported between saponins and cetyltrimethylammonium bromide or sodium dodecyl sulfate 5 .…”
Section: Introductionmentioning
confidence: 99%
“…3 On the other hand, the foaming power of mate saponin extract was better than polysorbate 80 and sodium dodecyl sulfate. 4 In a study on the effects of tea saponins and different synthetic surfactant mixtures on foam properties, a synergistic effect was reported between saponins and cetyltrimethylammonium bromide or sodium dodecyl sulfate. 5 Canto et al 6 examined the effects of five different electrolytes on foams produced using mate saponin and reported that the foaming power of the saponins did not change according to the electrolytes except for magnesium chloride.…”
Section: Introductionmentioning
confidence: 99%
“…Foams are often characterized in terms of foamability, which is defined as the capability of the chemicals to create foam regardless of the particular foam features, and foam stability, which describes the fluctuations in foam height or mass during the period shortly after foam production. 148,149 The foam was created using a sparger for measurements of foamability, morphology, foam quality, and rheology. Researchers also made a glass bead pack that they used to make foam by injecting gas and surfactants at the same time for foam stability.…”
Section: Foamability and Foam Stabilitymentioning
confidence: 99%
“…Except for Triton X-405, Zonyl FSO, and Hitenol H-10, all surfactants have shown good foamability and foam stability with increasing surfactant concentrations. Foams are often characterized in terms of foamability, which is defined as the capability of the chemicals to create foam regardless of the particular foam features, and foam stability, which describes the fluctuations in foam height or mass during the period shortly after foam production. , The foam was created using a sparger for measurements of foamability, morphology, foam quality, and rheology. Researchers also made a glass bead pack that they used to make foam by injecting gas and surfactants at the same time for foam stability. , Figure shows a simple configuration of the instrument utilized, and a glass frit is used in this setup .…”
Section: Foamability and Foam Stabilitymentioning
confidence: 99%
See 1 more Smart Citation